Implementing Screening, Brief Intervention and Referral Intervention for Health Promotion and Disease Prevention in Hospital Settings in Alberta: A Pilot Study - Kamala Adhikari; Kamala Adhikari; Muhammad Kashif Mughal; James Whitworth; Madison Bischoff; Gary F. Teare; Gary F. Teare (Frontiers Media S.A., 2023)
Objective: This study assessed the feasibility of implementing screening, brief intervention and referral (SBIR) intervention in hospital settings.Methods: This cross-sectional study evaluated the implementation of the SBIR intervention in a hospital in Alberta for tobacco use, alcohol intake, physical inactivity, and insufficient vegetable and fruit consumption. Patients were interviewed approximately 4-month later to collect data on the acceptability and effectiveness of the intervention received (n = 108). The data were primarily analyzed using descriptive statistics.Results: Of 108 patients, >80% agreed that "they were ok with being screened" for the risk factors during their hospital visit. Up to 68% of patients recalled the provider's brief education. At the follow-up, 20% of patients quit tobacco, 50% reduced alcohol use, 30% increased physical activity, and 25% increased vegetable and fruit intake.Conclusion: Risk factor screening was acceptable for patients. Patients recalled the brief education they received from healthcare providers. Patients reported risk-reducing changes in their risk factors. Our future work will integrate the SBIR approach within the Electronic Clinical Information System and use robust research methods to investigate the impact of SBIR on patients' behavior change.